Are psychological debriefing groups after a potential traumatic event suitable to prevent the symptoms of PTSD?. (May 2022) - Vignaud, Philippe; Lavallé, Layla; Brunelin, Jérôme; Prieto, Nathalie
Highlights: Psychological group debriefing (PDG) does not seem to have any effect on PTSD symptoms. PDG could have a positive effect on nonspecific symptoms of PTSD. Methodological quality of the studies evaluating PDG is heterogeneous. Further studies better considering the key features of PDG are required. Abstract: Psychological debriefing is a psychotherapeutic approach developed for early intervention in civilians and professionals who have to cope with a potential traumatic event (PTE). Although initial works claimed that this approach may decrease symptoms of posttraumatic stress disorder (PTSD), some studies have concluded that the clinical benefits of psychological debriefing were limited. Several methodological variations could explain the discrepancies observed among studies. Among these variations, how the approach is administered to participants should have importance, and clinical evidence suggests that debriefing groups instead of individuals could have a beneficial clinical effect. We conducted a systematic search of the literature investigating the clinical effects of psychological debriefing groups on PTSD symptoms after a PTE according to the PRISMA guidelines. Among the 790 articles found, 11 met our inclusion criteria. Most of these articles did not support any beneficial effect of psychological debriefing groups on PTSD symptoms. A large number of methodological variations that may influence the outcomes of these studies were observed. Psychological debriefing groups did not seem efficient in alleviating PTSD symptoms. Further studies of high methodological quality are needed to elucidate the effect of psychological debriefing groups on specific PTSD symptoms and on nonspecific symptoms.